Structural properties and hyperfine characterization of Sn-substituted goethites - Larralde, Ana Laura (2012)
Tin-doped goethites obtained by a simple method at ambient pressure and 70 ◦C were characterized by inductively coupled plasma atomic emission spectrometry, scanning electron microscopy, Rietveld refinement of powder X-ray diffraction data, and 57Fe and 119Sn Mössbauer spectroscopy. The particles size and the length to width ratios decreased with tin-doping. Sn partially substituted the Fe(III) ions provoking unit cell expansion and increasing the crystallinity of the particles with enlarged domains that grow in the perpendicular and parallel directions to the anisotropic broadening (1 1 1) axis. Intermetallic E, E and DC distances also change although the variations are not monotonous, indicating different variations in the coordination polyhedron. In general, the Sn-substituted samples present larger intermetallic distances than pure goethite, and the greatest change is shown in the E distance which coincides with the c-parameter. 119Sn Mössbauer spectroscopy revealed that Sn(II) is incorporated as Sn(IV) in the samples. On the other hand, Fe(II) presence was not detected by 57Fe Mössbauer spectroscopy, suggesting the existence of vacancies in the Sn-doped samples. A lower magnetic coupling is also evidenced from the average magnetic hyperfine field values obtained as tin concentration increased.